Analisis Dampak Budaya Organisasi dan Kompetensi dalam Meningkatkan Kinerja Pegawai DISDIK Jawa Barat - Sholihannisa, Lulu Ulfa (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
This research aims to analyze the impact of organizational culture and competence on employee performance at the West Java Ministry of Education, both simultaneously and partially. The method used is a descriptive-verificative method, with the population being the employees at the West Java Ministry of Education and a sample of 50 people, in addition to using primary data. This research yields an average interpretation of the organizational culture variable at 3.75%, the competence variable at 3.75%, and the employee performance variable at 3.82%. The analysis using path analysis shows that there is a positive and highly significant influence of organizational culture and competence on employee performance at the West Java Ministry of Education, both partially and simultaneously, amounting to 60.8%.